PERAN ASAM AMINO DALAM MENDUKUNG FUNGSI SISTEM IMUN DAN KETAHANAN TUBUH: LITERATURE REVIEW - Nursia Marsaulina Panjaitan; Manna Wa Salwa; ⁠Meliana; Jihan Nur Asyfa Hanafi; ⁠ ⁠Aulia Nurmala Sari Sikumbang (STKIP Subang, 2026)
Amino acids play a crucial role in supporting immune system function and bodily defense. This study aims to comprehensively review the roles of various amino acids including glutamine, arginine, branched-chain amino acids (BCAAs), serine, glycine, and tryptophan in regulating both innate and adaptive immune responses at the cellular and molecular level. This research employed a qualitative approach through a systematic literature review method. Data were sourced from scientific journals and publications accessed via Google Scholar, PubMed, and ScienceDirect using relevant keywords. Results showed that glutamine serves as the primary energy source for active immune cells by producing ATP and supporting glutathione synthesis. Arginine modulates inflammatory balance through dual iNOS and arginase pathways, producing nitric oxide (NO) and polyamines respectively. BCAAs, particularly leucine, activate the mTORC1 signaling pathway that promotes proliferation of T cells and dendritic cells. Serine and glycine provide nucleotide precursors via the SGOC pathway and act as antioxidants through glutathione formation, while tryptophan suppresses hyperinflammation through the kynurenine pathway involving IDO1 and AhR receptor activation. No amino acid functions independently; all operate in an integrated metabolic network. Thus, concluded that adequate intake and balance of amino acids are essential for optimal immune system function, and that amino acid-based immunonutrition strategies represent a promising approach in clinical therapy for various conditions including sepsis, autoimmune diseases, and critical illness.